Wage structure effects of international trade: Evidence from a small open economy - Philip Du Caju; Francois Rycx; Ilan Tojerow (Institute for the Study of Labor (IZA), 2011)
In the last decades, international trade has increased between industrialised countries and between high- and low-wage countries. This important change has raised questions on how international trade affects the labour market. In this spirit, this paper aims to investigate the impact of international trade on wage dispersion in a small open economy. It is one of the few to: i) use detailed matched employer-employee data to compute industry wage premia and disaggregated industry level panel data to examine the impact of changes in international trade on changes in wage differentials, ii) simultaneously analyse both imports and exports, and iii) examine the impact of imports according to the country of origin. Looking at the export side, we find (on the basis of the system GMM estimator) a positive effect of exports on industry wage premia. The results also show that import penetration has a significant and negative impact on industry wage differentials whatever the country of origin. However, the country of origin appears to matter quite a lot. Indeed, the detrimental effect of imports on wages is found to be significantly bigger when the latter come from low-income countries than from high-income countries.
urn:nbn:de:101:1-201104134205
Keywords: F16; J31; 330; wage structure; inter-industry wage differentials; international trade; matched employer-employee data; Lohnstruktur; Branche; Außenwirtschaft; Export; Import; Kleines-offenes-Land; Schätzung; Belgien